The characteristic of lethality as an indicator of combinad infections - V. V. Nechaev; A. K. Ivanov; I. P. Fedunyak; V. B. Musatov; M. N. Pogromskaja; A. B. Bubochkin; L. N. Pozhidaeva; A. A. Sacra (Журнал инфектологии, 2016)
The Combined Socially Important Infections (CSII) in St. Petersburg are result of accumulation of chroniogenic potential of HIV infection, tuberculosis and chronic viral hepatitis B and C. The analysis of a lethality from the combined infection (CI) for the long-term period in dynamics by years, showed to age and sexual groups and other signs that it exceeds that from tuberculosis by 2,4 times, from chronic hepatitis by 7,5 times. High level of a lethality of persons of young age, sharp growth of tuberculosis of intra chest, intra belly lymph nodes, frequent generalization of process with involvement in process of a liver, a spleen, kidneys testifies to the leading role of HIV infection in failures of diseases. The system and algorithm of proofs about the reasons of lethal outcomes of SI have to be based on representative selections. For this purpose it is necessary to carry out registration of HIV infection not only in the AIDS centers, but also regional in the form of the uniform register SI (HIV+TB+HIC or HIB) for the purpose of complex impact on epidemic process.